Highly durable polybenzimidazole composite membranes with phosphonated graphene oxide for high temperature polymer electrolyte membrane fuel cells - Abouzari-Lotf, E. (2019)
Polymer electrolyte membranes with highly stable phosphoric acid loading continue to pose a challenge for the development of durable high temperature polymer electrolyte membrane fuel cells. A new class of highly conductive and durable composite membranes is prepared for high temperature fuel cell application under anhydrous conditions. 2,6-Pyridine functionalized polybenzimidazole (Py-PBI) is used as substrate for hosting phosphoric acid moiety. A highly dispersible phosphonated graphene oxide (PGO) introduced to Py-PBI substrate at different levels prior to acid doping and conductivity, durability and fuel cell performance of developed membranes are evaluated. A proton conductivity as high as 76.4 Ã 10â3 S cmâ1 is achieved at 140 Â°C under anhydrous condition. A strong correlation is found between the content of PGO and the stability of the acid content despite similarity in doping level. In general, the conductivity is obviously more stable in the PGO containing membranes. A Pt-catalyzed fuel cell using the developed composite membranes show a peak power density >359 mW cmâ2 at 120 Â°C under anhydrous condition which is above 75 improvements compared to the membranes without the phosphonated filler. This work demonstrates that the adopted membrane preparation strategy and their observed properties pave the way for highly conductive and durable proton conducting membranes. Â© 2018 Elsevier B.V.